The Impact of Kampus Mengajar Program on Teaching and Learning - Ismail, Resti; Slamat, Tri Anawiah H; Wabula, Vidian (Huele: Journal of Applied Linguistics, Literature and Culture, 2024)
The Kampus Mengajar Program, an integral component of Indonesia's Independent Campus initiative, represents a strategic approach to educational enhancement through university student involvement in elementary education. This qualitative study investigated teachers' perceptions regarding the role and impact of Kampus Mengajar students in facilitating the learning process at SD Negeri 84 Ambon. The research employed structured interviews with purposively selected participants, including classroom teachers from grades one through six, a shadow teacher, and the school principal, to gather comprehensive insights into the program's implementation and effectiveness. Data analysis followed a systematic qualitative approach, involving thorough transcription and thematic analysis of interview responses. The findings revealed four key dimensions of program impact: successful implementation of innovative teaching strategies, particularly through technology integration; significant enhancement of student learning outcomes, especially in literacy and digital competencies; development of effective teacher-student collaborative relationships; and improvement in school administrative processes. These outcomes demonstrate the program's effectiveness in enhancing educational quality through structured student involvement while providing valuable insights for future program implementation and educational policy development in Indonesia.